IP based content delivery over Next Generation Networks - Gomes, Diogo (2008)
Trends towards Next Generation Networks (NGN) are also changing the fundamental nature of TV services. Entertainment is becoming an increasingly participative experience, both with user feedback, and with user-generated content. Furthermore, the diversity of delivery mechanisms is increasing, reaching the mobile environment. The diversity of actors and technologies is now leading to a trend into IP-based content delivery, as a solution to heterogeneity management. We present an architecture for future environments, which bridges the gap between the content production and communication infrastructures, able to operate across different networks. This architecture resorts to the notion of Service Enablers deployed above evolved converged multimedia networks, based on the IP protocol. We demonstrated this architecture by laboratory prototyping.